COMPARING CHATGPT AI ADOPTION IN HIGHER EDUCATION: EVIDENCE FROM UNIVERSITIES IN INDONESIA AND MALAYSIA - Tri Astuti; Muhammad Nazil Iqdami; Heri Triluqman BS; Haryono BS; Chau Kien Tsong (Jurnal Informatika Teknologi dan Sains (Jinteks), 2026)
The rapid development of Generative Artificial Intelligence (GenAI), particularly ChatGPT, has transformed learning practices in higher education by supporting various academic activities. This study compared ChatGPT adoption among university students in Indonesia and Malaysia using a quantitative cross-sectional survey. Data were collected from 211 undergraduate students (186 from Indonesia and 25 from Malaysia) through an online questionnaire. Descriptive statistics and Independent Samples t-tests were used to examine differences in Awareness & Access, Academic Usage, Self-Efficacy, and Perceived Benefits. The results showed high levels of ChatGPT adoption in both countries, with mean scores above 4.00 across all dimensions. Although Malaysian students reported slightly higher mean scores, no statistically significant differences were found between the two groups (p > 0.05). Students primarily used ChatGPT to search for information, complete academic assignments, generate ideas, and improve learning efficiency. These findings indicate a similar pattern of ChatGPT adoption across universities in Indonesia and Malaysia and underscore the importance of institutional AI policies, AI literacy, and ethical AI integration to support digital transformation in higher education.